FUMEPOC: Early detection of chronic obstructive pulmonary disease in smokers - Fernández Antonio; Yarza-Cañellas Manuel; Soler Juan J; Vela-Troncoso María P; López-Pineda Adriana; Lorca-Amorrich Patricia; Plaza-Sirvent Carlos; Carratala Munuera Concepcion V; Orozco-Beltrán Domingo; Gil-Guillén Vicente; Rosado-Bretón Luis; Olivares-Bautista Carmen; et al. (BMC, 2011)
Abstract Background Currently is not feasible using conventional spirometry as a screening method in Primary Care especially among smoking population to detect chronic obstructive pulmonary disease in early stages. Therefore, the FUMEPOC study protocol intends to analyze the validity and reliability of Vitalograph COPD-6 spirometer as simpler tool to aid screening and diagnosis of this disease in early stages in primary care surgery. Methods / Design Study design: An observational, descriptive study of diagnostic tests, undertaken in Primary Care and Pneumology Outpatient Care Centre at San Juan Hospital and Elda Hospital. All smokers attending the primary care surgery and consent to participate in the study will undergo a test with Vitalograph COPD-6 spirometer. Subsequently, a conventional spirometry will be performed in the hospital and the results will be compared with those of the Vitalograph COPD-6 test. Discussion It is difficult to use the spirometry as screening for early diagnose test in real conditions of primary care clinical practice. The use of a simpler tool, Vitalograph COPD-6 spirometer, can help in the early diagnose and therefore, it could improve the clinical management of the disease.